Penurunan Kata dengan Morfem Unik - Nazir, Yuniar Nuri (Ruang Kata, 2025)
This study aims to describe the process and characteristics of word derivation with unique morphemes in Indonesian. The research is motivated by the limited specific studies on this morphological phenomenon, necessitating a comprehensive description to enrich the linguistic treasury of Indonesia. A qualitative descriptive approach was employed, with structural theory as the analytical foundation. Data were collected through field survey, observation, and elicitation methods in Suralaga District, East Lombok, while data analysis used the distributional method with substitution techniques. The results indicate that the process referred to as "word derivation" is essentially a compounding process, where a unique morpheme is combined with a base morpheme to form a compound word. The unique morpheme functions as the attached element, while the base morpheme serves as the host element. This study identified ten constructions, such as kering kerontang (dry as a bone) and gelap gulita (pitch dark), which demonstrate the unique and syntactically bound nature of their constituent morphemes. These findings provide a theoretical contribution to Indonesian morphology and practical implications for language teaching.